Rotavirus gastroenteritis in Medan (part four) - Achmad Razali; Ahmad Jufri; Mansur Karo Karo; A. H. Sutanto; Helena Siregar (Paediatrica Indonesiana, 1984)
From April to May 1982, 59 children with gastroenteritis, aged 0 - 3 years (34 males and 25 females) had been examined for Rotavirus at the Department of Child School of Medicine, University of North Sumatera/Dr. Pirngadi General Hospital, Medan. Rotavirus detection was done with the Elisa method. It was found that 32 patients (54.24%) had Rotavirus in their feces. The youngest patient was 2 days old. Vomiting was more pronounced in the Rotavirus group. Degree of temperature did not differ significantly in both groups. From the 32 Rotavirus patients, 71.81% was bottle fed and 28,12% breast fed. From the bottle fed infants with diarrhoea, there were 23 (79,31 %) patients with Rotavirus. From the 21 breast fed patients with diarrhoea, there were only 9 (42,85%) infants with Rotavirus.